Wine, wealth, and the state in late antique Egypt : the house of Apion at Oxyrhynchus - Hickey, T. M. (New texts from ancient cultures., 2012)
The "glorious house" of the senatorial family of the Flavii Apiones is the best documented economic entity of the Roman Empire during the fifth through seventh centuries, that critical period of transition between the classical world and the Middle Ages. For decades, the rich but fragmentary manuscript evidence that this large agricultural estate left behind, preserved for 1,400 years by the desiccating sands of Egypt, has been central to arguments concerning the agrarian and fiscal history of Late Antiquity, including the rise of feudalism. Wine, Wealth, and the State in Late Antique Egypt is the most authoritative synthesis concerning the economy of the Apion estate to appear to date. T.M. Hickey examines the records of the family's wine production in the sixth century in order to shed light on ancient economic practices and economic theory, as well as on the wine industry and on estate management. Based on careful study of the original manuscripts, including unpublished documents from the estate archive, he presents controversial conclusions, much at odds with the "top down" models currently dominating the scholarship.